Respuesta :

x^2b + t = x^2e

x^2e - x^2b = t

x^2(e - b) = t

x^2 = t /(e -b)

x = √[t /(e -b)] or x = - √[t /(e -b)]

Answer:

[tex]x = \sqrt{\frac{t}{(e - b)} }[/tex], [tex]x = - \sqrt{\frac{t}{(e - b} }[/tex]

Step-by-step explanation:

[tex]x^{2} b + t = x^{2} e[/tex]

To solve this equation for x, arrange the like terms together by placing the two terms with variable [tex]x^{2}[/tex] at one side of the equation and the remaining terms at the other side of the equation:

[tex]x^{2} e - x^{2} b = t[/tex]

Now take the common terms out and write it as:

[tex]x^{2} (e - b) = t[/tex]

[tex]x^{2} = \frac{t}{e - b}[/tex]

Now take square root on both sides:

[tex]\sqrt{x^{2}} = \sqrt{\frac{t}{e - b}}[/tex]

[tex]x = \sqrt{\frac{t}{(e - b)}}[/tex] , [tex]x = - \sqrt{\frac{t}{(e- b)}}[/tex]

ACCESS MORE